2012
DOI: 10.5194/acpd-12-14115-2012
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Overview of the LADCO winter nitrate study: hourly ammonia, nitric acid and PM<sub>2.5</sub> composition at an urban and rural site pair during PM<sub>2.5</sub> episodes in the US Great Lakes region

Abstract: An overview of the LADCO (Lake Michigan Air Directors Consortium) Winter Nitrate Study (WNS) is presented. Sampling was conducted at ground level at an urban-rural pair of sites during January–March 2009 in eastern Wisconsin, toward the Western edge of the US Great Lakes region. Areas surrounding these sites experience multiday episodes of wintertime PM2.5 pollution characterized by high fractions of ammonium nitrate in PM, low wind speeds, and air mass stagnation. Hourly surface monitoring of inorg… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 52 publications
(10 reference statements)
2
27
0
Order By: Relevance
“…It is well-established that winter conditions (including long nights, lower temperatures and boundary layer height, and higher humidity) promote the formation of secondary NH 4 NO 3 . 43,44 The summertime minimum may be partially enhanced to negative sampling artifacts whereby ammonium nitrate volatilizes as ammonia and nitric acid from Teflon filters during periods of elevated temperatures. 45 These seasonal variations of NH 4 + and NO 3 − are consistent with a greater trend across the US.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-established that winter conditions (including long nights, lower temperatures and boundary layer height, and higher humidity) promote the formation of secondary NH 4 NO 3 . 43,44 The summertime minimum may be partially enhanced to negative sampling artifacts whereby ammonium nitrate volatilizes as ammonia and nitric acid from Teflon filters during periods of elevated temperatures. 45 These seasonal variations of NH 4 + and NO 3 − are consistent with a greater trend across the US.…”
Section: Resultsmentioning
confidence: 99%
“…5b) when low temperatures and longer nights promote the formation of secondary NH 4 NO 3 . 43, 44 This factor accounted for 17–24% of PM 2.5 mass at the monitoring sites with maximum contributions occurring in winter (Table 2). A minor rural enhancement (1.03) in the secondary nitrate PMF factor was detected in PMF model results, but is not consistent with the urban enhancement in ambient nitrate concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Particulate NH 4 increased at all but one site and increases in NO 3 are closely correlated with the increases in NH 4 (r 2 ¼ 0.84) although the regression fit shows a 2.3 mg/m 3 increase in NO 3 for each 1 mg/ m 3 increase in NH 4 , well below the 3.4:1 NO 3 /NH 4 molar mass ratio for NH 4 NO 3 . Stanier et al (2012) studied winter NO 3 episodes in Wisconsin and identified a relationship between elevated NO 3 , snow cover and near freezing temperatures which promote fog formation and stabilization of the boundary layer. While the causality chain resulting in the winter NO 3 episodes remains uncertain, it is interesting to note that the 2009e2010 winter was exceptionally snowy in many parts of the eastern U.S., including the Midwest (NCDC, 2010), thus suggesting the conditions found by Stanier et al to be favorable for elevated NO 3 concentrations may have been more prevalent in 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Although a number of important issues are specific to polluted wintertime environments, detailed wintertime intensive field studies are less common. Accumulation of aerosol mass in excess of National Ambient Air Quality Standards (NAAQS, currently 35 µg m –3 for PM 2.5, particulate matter (PM) less than 2.5 µm diameter, 24 h average), particularly ammonium nitrate aerosols, tends to be a winter phenomenon due to the temperature‐dependent phase partitioning of nitric acid and ammonia [ Chen et al ., ; Chen et al ., ; Fischer and Talbot , ; Katzman et al ., ; Mathur et al ., ; Schaap et al ., ; Stanier et al ., ; Tolocka et al ., ; Yu et al ., ]. Air quality models often fail to accurately predict nitrate aerosol, due to the complexity of both the chemistry and the shallow boundary layers typically associated with these episodes.…”
Section: Introductionmentioning
confidence: 99%